The views of American Multinational CEOs on Internationalized Business Education for Prospective Employees - Ball, Donald A.; McCulloch, Wendell H. (Journal of International Business Studies, 1993)
For some time, a number of industry leaders have been exhorting American business schools to train their students in the aspects of international business. As late as 1987, a group of prominent leaders from business, labor, academia and government issued a report that stated that business schools must internationalize the entire course of study and should include comparative business practices, foreign languages and analyses of other countries and cultures.